2018
DOI: 10.1542/peds.2018-2095
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Iron Deficiency in Early Childhood Using Serum Ferritin in the Primary Care Setting

Abstract: on behalf of the TARGet Kids! Collaboration OBJECTIVES: The American Academy of Pediatrics recommends universal screening for anemia using hemoglobin at 12 months. However, hemoglobin lacks diagnostic accuracy for iron deficiency, and the optimal age for screening has not been determined. Our objective was to assess a screening strategy for iron deficiency using serum ferritin. METHODS: We conducted a cross-sectional study of children 1 to 3 years old attending a health supervision visit. We examined the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…During the first stages of iron deficiency, ferritin levels—reflecting the iron stores—drop faster, while hemoglobin remains normal. As a consequence, measuring serum ferritin is suggested to detect non-anemic iron deficiency, especially in children with ASD and sleep disorders [ 18 , 167 , 168 ], even if false increases in ferritin levels are possible because ferritin is an acute-phase reactant [ 169 ].…”
Section: Oral Over-the-counter Medicinesmentioning
confidence: 99%
“…During the first stages of iron deficiency, ferritin levels—reflecting the iron stores—drop faster, while hemoglobin remains normal. As a consequence, measuring serum ferritin is suggested to detect non-anemic iron deficiency, especially in children with ASD and sleep disorders [ 18 , 167 , 168 ], even if false increases in ferritin levels are possible because ferritin is an acute-phase reactant [ 169 ].…”
Section: Oral Over-the-counter Medicinesmentioning
confidence: 99%
“…All models were adjusted for all prespecified covariates regardless of statistical significance 27. Restricted cubic spline analysis was used to test for a non-linear relationship between age and serum ferritin and then confirmed by loess curves, selecting three knot points to correspond to the age at scheduled visits (15, 18 and 24 months) 28. Multiple imputation using the fully conditional specification method was used to handle missing data.…”
Section: Methodsmentioning
confidence: 99%
“…We selected the 18-month visit, as our previous analysis showed that the serum ferritin level is lowest between 15 and 24 months and that the hemoglobin level does not change substantially between 12 and 24 months. 15 Finally, Shaker and colleagues 47 included the cost of use of additional health care services for children with untreated iron deficiency, whereas we did not.…”
Section: Open Researchmentioning
confidence: 99%
“…The estimates used for our base case came from 2 published randomized controlled trials and a long-term observational study (Table 1). 6,12,15 Untreated iron deficiency in infancy is associated with poor neurodevelopmental and functional outcomes. 5,11,12,36 Lozoff and colleagues 6 reported that, at 10 years of age, compared to children with good iron status in infancy, children with chronic, severe iron deficiency in infancy had higher rates of grade repetition (26% v. 12%) and referral for special services (21% v. 7%).…”
Section: Openmentioning
confidence: 99%
See 1 more Smart Citation